A Study on Prevalence of Selected Mental Disorders (Anxiety, Depression, Dementia) Among Residents of Old Age Home in Jabalpur City, Madhya Pradesh, India - Chaudhari, Ketulkumar; Rai, Neeraj; Tiwari, Rajesh (National Journal of Community Medicine, 2022)
Ageing is a normal phenomenon and an inescapable process. According to W.H.O. Worldwide over 20% of adults aged 60 and over suffer from a mental or neurological disorder and according to the National Mental Health Survey of India (2015-16) the prevalence of mental disorders in geriatric population in the country is 10.90%. Thus, this study aims to assess anxiety, depression and cognitive disorders among persons living in OAH and to explore the various factors associated with it. A descriptive cross-sectional study was conducted in OAH Jabalpur. All residents of OAH were included in the study so no need for sampling. The sample size was 73. A Predesigned semi-structured Questionnaire was used which comprised of the socio-demographic profile with using GAD-7, GDS-15 & MMSE-30 for screening of psychiatric morbidity. Data analysis was done by using IBM SPSS-21. The result shows the mean age of the study subject was 72.14 ±7.482. The prevalence of Anxiety was 19.2%, prevalence of depression was 41.1% and prevalence of cognitive impairment was 23.3%. In this study it was found out that older adults suffering from anxiety, depression and cognitive impairment, most of older adults was widowed and there is a need to provide psychological support, a positive environment and proper care to improve mental health.